Roadmap on solar water splitting: current status and future prospects. Issue 2 (28th September 2017) - Chu, Sheng; Li, Wei; Yan, Yanfa; Hamann, Thomas; Shih, Ishiang; Wang, Dunwei; Mi, Zetian
Abstract: Artificial photosynthesis via solar water splitting provides a promising approach to storing solar energy in the form of hydrogen on a global scale. However, an efficient and cost-effective solar hydrogen production system that can compete with traditional methods using fossil fuels is yet to be developed. A photoelectrochemical (PEC) tandem cell consisting of a p-type photocathode and an n-type photoanode, with the photovoltage provided by the two photoelectrodes, is an attractive route to achieve highly efficient unassisted water splitting at a low cost. In this article, we provide an overview of recent developments of semiconductor materials, including metal oxides, nitrides, chalcogenides, Si, III–V compounds and organics, either as photocathodes or photoanodes for water reduction and oxidation, respectively. In addition, recent efforts in constructing a PEC tandem system for unassisted water splitting are outlined. The importance of developing a single-photon photocathode and photoanode that can deliver high photocurrent in the low bias region for efficient PEC tandem system is highlighted. Finally, we discuss the future development of photoelectrode materials, and viable solutions to realize highly efficient PEC water splitting device for practical applications.